1996
DOI: 10.1016/0014-5793(96)00179-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is triggered by the cyclic AMP signalling pathway in renal mesangial cells

Abstract: Glomerular mesangial cells are regarded as specialized smooth muscle cells located within the renal glomeruli and fulfilling important functions in glomerular physiology and pathophysiology. Here, we report that activation of the cyclic AMP signalling pathway by dibutyryl cyclic AMP, forskolin, or the ~2-adrenergic receptor agonist salbutamol results in induction of apoptosis in mesangial cells. Activation of the apoptotic programme results in DNA fragmentation which is visible for most forms of apoptosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In this complex scenario, reports have indicated that PKA signaling could drive apoptosis of lymphoid cells that involve mitochondrion-mediated cascades, thus suggesting the interplay of multitudes of genes with a network of cellular pathways (42,70). In this regard, M. bovis BCGdriven expression of apoptotic genes Puma, Noxa, Bid, Bim, Bak1, and Smac in macrophages could be effectively blocked by pharmacological inhibition of PKA (Myr-PKI-␣ or KT5720) (Fig.…”
Section: Mir-155 Induces Macrophage Apoptosismentioning
confidence: 95%
“…In this complex scenario, reports have indicated that PKA signaling could drive apoptosis of lymphoid cells that involve mitochondrion-mediated cascades, thus suggesting the interplay of multitudes of genes with a network of cellular pathways (42,70). In this regard, M. bovis BCGdriven expression of apoptotic genes Puma, Noxa, Bid, Bim, Bak1, and Smac in macrophages could be effectively blocked by pharmacological inhibition of PKA (Myr-PKI-␣ or KT5720) (Fig.…”
Section: Mir-155 Induces Macrophage Apoptosismentioning
confidence: 95%
“…However, in case of severe DNA damage, p53 also signals apoptosis in at least some types of cells. Intriguingly, not all cells expressing inducible NO synthase activity, such as rat mesangial cells (13), are toxicologically affected. Cellular susceptibility toward NO varies between different types of cells and tissues.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…Some investigators have reported that cAMP and cGMP analogs cause apoptosis, e.g. in renal mesangial cells 3 and lymphoblastic leukemia cells; 4 while other studies have shown that cAMP and cGMP analogs prevent apoptosis in other cell types, such as neutrophils, 5 hepatocytes, 6,7 smooth muscle cells, 8 promonocytic leukemia cells, 9 and human endothelial cells. 10 We and others have demonstrated that nitric oxide (NO)-mediated hepatoprotective effects are partially dependent on cGMP production because NO stimulates soluble guanylyl cyclase, and inhibitors of the soluble guanylyl cyclase pathway that functions to partially suppress the protective actions of NO.…”
Section: Introductionmentioning
confidence: 98%